IS MUSCULAR AND FUNCTIONAL PERFORMANCE RELATED TO GAIT SYMMETRY IN OLDER ADULTS? A SYSTEMATIC REVIEW - Guadagnin, Eliane C; Barbieri, Fabio A [UNESP]; Simieli, Lucas [UNESP]; Carpes, Felipe P (Elsevier, 2019)
Background: Gait asymmetries are a matter of discussion concerning gait adaptation in older adults. While most studies perform unilateral gait assessments, the hypothesis that asymmetry in gait biomechanics is influenced by muscular and functional performance in older people needs to be confirmed. Purpose: Here we performed a systematic review (CRD42018093189) to discuss the relationship between muscular and functional performance and gait asymmetries in older adults. Materials and Methods: Searches were performed using Medline via Pubmed, Scopus, PEDro, Cochrane Central, and Lilacs databases. Studies investigating leg asymmetries during overground locomotion and recording kinetics, kinematics or muscular activation parameters to determine at least one muscular or functional parameter were included. Results: Findings show that gait asymmetries, especially in step temporal parameters, are mainly related to functional outcomes, but the relationship with muscular performance was not possible to determine. Conclusions: The relationship of gait asymmetry with muscular performance is still unknown, and there is a lack of investigations. Improvements in performance of functional tasks lead to a more symmetric gait.
Keywords: Aging; Asymmetry; Functional laterality; Motor control; Walking